2021
DOI: 10.1108/ohi-11-2020-0165
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of indoor environment evaluation for The Springs development in Dubai, UAE

Abstract: Purpose This study aims to evaluate The Springs’ indoor environment, one of the iconic townhouse-type residential buildings in Dubai, more efficiently for the integrated evaluation of the indoor environment with the weights of indoor environmental factors such as thermal, indoor air, lighting and acoustic. Design/methodology/approach The weights of the indoor environment factors were derived for the integrated evaluation to reflect the residents’ preferences. Based on the post-occupancy evaluation (P.O.E.) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…This is in line with the study by Zhang et al (2022), which found that the indoor environment of sports buildings directly impacts the well-being and comfort of occupants, including athletes, spectators and staff. Evaluating the environmental performance of sports buildings provides an opportunity to engage the community in sustainable practices and inspire behaviour change (Jung et al , 2021; Sant'Anna et al , 2018).…”
Section: The Analysis and Discussion Of Findingsmentioning
confidence: 99%
“…This is in line with the study by Zhang et al (2022), which found that the indoor environment of sports buildings directly impacts the well-being and comfort of occupants, including athletes, spectators and staff. Evaluating the environmental performance of sports buildings provides an opportunity to engage the community in sustainable practices and inspire behaviour change (Jung et al , 2021; Sant'Anna et al , 2018).…”
Section: The Analysis and Discussion Of Findingsmentioning
confidence: 99%
“…The building materials used in this study were the flooring and wallpaper used the most as interior finishing materials (Arar & Jung, 2021; Jung et al, 2021). Table 1 is an overview of experimental building materials.…”
Section: Methodsmentioning
confidence: 99%
“…In Dubai, studies about indoor environment are indirectly related to BD, such as (Nazzal, 2015; Jung et al ., 2021). It is expected that more research will be conducted in the future, in line with the new vision to improve the quality of living in Dubai's 2040 urban master plan launched in 2021 (The United Arab Emirates' Governmental Portal, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%